2011
DOI: 10.1603/me10182
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lyme Disease Agents and Several Emerging Pathogens in Questing Ticks From the German Baltic Coast

Abstract: In summer 2008, a total of 512 Ixodes ricinus (Acari: Ixodidae) ticks was collected from vegetation in four areas at the Baltic coast of Germany and tested for the presence of Lyme disease spirochetes. Among them, 293 ticks from three areas were screened for Anaplasma phagocytophilum (Rickettsiales: Anaplasmataceae), rickettsiae of the spotted fever group (Rickettsiales: Rickettsiaceae), and Babesia spp. (Piroplasmida: Babesiidae), respectively. Borrelia burgdorferi sensu lato genospecies (Spirochaetales: Spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
2
18
2
1
Order By: Relevance
“…The percentage of ticks infected with Babesia microti in own studies was 4.1%, and it was higher than that obtained by other European researchers (2,3,8).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The percentage of ticks infected with Babesia microti in own studies was 4.1%, and it was higher than that obtained by other European researchers (2,3,8).…”
Section: Discussioncontrasting
confidence: 68%
“…Among the biological agents causing occupational zoonoses, those transmitted by ticks (bacteria, viruses, protozoa) are of great importance because they cause dangerous infections in humans, often described as 'emerging zoonoses' (1)(2)(3)(4). Ticks (Ixodida) are known as vectors transmitting microbial pathogens from animals to humans, and the diseases caused by these microbes constitute a serious epidemiological problem, especially in the environment of forest exploitation and at agricultural work (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study, published by Hubálek et al [17], a total of 298 ticks were examined by dark field microscopy, from which 11.1% of the whole ticks collection were positive for the borreliae. A German study focusing on the federal state of Thuringia revealed only 6.1% prevalence of Bbsl in 618 collected samples analyzed by nested PCR and RFLP targeting a fragment of the ospA gene [18]. In the presented study, the lower number of successfully sequenced samples, especially in 2008 (28.6%), could have been caused by the small average G+C bases content in Bbsl genome.…”
Section: Discussionmentioning
confidence: 49%
“…One study showed that infestation rates in wooded recreational areas was as great as 7.4 ticks per person per hour (Faulde and Robbins 2008), resulting in relatively high risks of pathogen exposure. Often these ticks carry multiple pathogens, raising the possibility of a co-infection with a Borrelia species and another pathogen (Loebermann et al 2006, Pichon et al 2006, Hildebrandt et al 2010b, Franke et al 2011. In Europe, studies indicate a potentially higher prevalence of Babesia species infections than previously believed with higher levels of seroreactivity to Babesia antigens in 11% and 4.4% of people exposed to ticks in Germany and Poland, respectively (Hunfeld et al 2002, Pancewicz et al 2011.…”
Section: Introductionmentioning
confidence: 99%